تعريف بعض عزلات فيروس التبرقش الريشي للبطاطا الحلوة باستخدام النباتات الدالة التفريقية - عاقل إنصاف; اسماعيل عماد; الشعبي صلاح (Latakia University Journal -Biological Sciences Series, 2019)
أجريت هذه الدراسة لتحديد العزلات المختلفة لفيروس التبرقش الريشي على البطاطا الحلوة المُنتشرة في الساحل السوري، ومعرفة العزلات الشرسة والعزلات الهادئة تبعاً لردة فعل النباتات الدالة. استخدمت عقل بطاطا حلوة مصابة بفيروس البرقشة الريشية كطعوم للتطعيم على نباتات دلالة مختلفة. أظهرت النتائج اختلاف ردة فعل نفس النوع من النباتات الدالة مثل Ipomoea nil و I. setosa تجاه عقل مختلفة المصدر من البطاطا الحلوة المصابة بالفيروس والمجموعة من نفس المنطقة، وقد لوحظ أعراض فيروسية مختلفة عند تطعيم هذه النباتات بعقل بطاطا حلوة مصابة بفيروس التبرقش الريشي. أظهرت نباتات I. setosa درجات مختلفة من أعراض الموزاييك، الشحوب، تشوه الأوراق، التفاف الأوراق، تقزم النباتات، وقد أظهرت النتائج إمكانية تقسيم هذه العزلات إلى أربع مجموعات هي عزلات شديدة الشراسة ( تشوه وتقزم النبات)، عزلات شرسة ( شحوب النبات)، عزلات معتدلة الشراسة (التفاف الأوراق، موزاييك)، عزلات هادئة (بدون أعراض). هذه النتائج جديدة ومن المحتمل وجود أربع سلالات لفيروس التبرقش الريشي في المنطقة الساحلية. The study was conducted in order to determine different isolates of Sweet potato feathery mottle potyvirus in Syrian costal area, and for identification of the severe isolates and mild isolates. Infected sweet potato feathery mottle virus cuttings have been used as scion for grafting on different indicator plants. Results showed that different reaction on the same indicator plants as I. setosa, I. nil were observed showing different viruses symptoms when these plants was grafted by SPFMV infected scion. Moreover I. setosa plants showed various degrees of mosaic, chloroses, leaf malformation, leaf curling, and stunting symptoms, so these isolates could be divided into four a groups: very severe isolate (leaf malformation, stunting), severe isolate (chloroses), mild isolate (mosaic and leaf curl), symptomless . These results are new, and it is possible that four strains of SPFMV are present in the coastal region.